Le modèle de la société de l’information au Royaume-Uni et en Écosse - Lise-Marie Couronne-Geary (Netcom)
As soon as he came to power, Tony Blair linked the challenge of information and communication technologies to state and public services reforms, and placed the central state at the heart of a British-style information society. If centralisation is undoubtedly one of the most characteristic features of that model, it is actually uneven, varying according to the matter in question (be it market regulation or e-learning policies for instance), and also, more interestingly, according to the area or territory concerned.